Analysis of Communication Privacy Management on TikTok - Gabriella Nikita; Sandi Dwi Ariadi; Timotius Christian (Dinasti International Journal of Education Management And Social Science, 2025)
Social media is a digital platform that allows people to create, share and exchange information, ideas and content in various formats, such as text, images, video and audio. It allows people and groups to interact over the internet, allowing them to interact with each other in real time or asynchronously. This research aims to find out how Gen-Z carries out privacy management on the TikTok application. The research was conducted qualitatively by conducting in-depth interviews with a total of three informants with an analysis method using Communication Privacy Management (CPM) theory. The results of this research are that privacy settings in the TikTok application are important and must be maintained by users. The conclusion of this research is related to how users use privacy restrictions on their respective accounts. The results of the research findings can also provide theoretical implications, namely these findings can explain that issues related to privacy in an application like TikTok are very important and as a user you must understand this before or when using the application. The practical implications are that TikTok users can take advantage of the features provided by the application as an effort to protect the privacy of their communications.